Correct question:
Evaluate the expression below for x = 2, y = –3, and z = –1.
Given:
Options:
A.–23
B.–5
C.13
D.27
Answer:
B. -5
Explanation:
In this question we are given the following values:
x = 2
y = -3
z = -1
Given the expression:
To evaluate, let's substitute for 2, -3 & - 1 for x, y & z respectively
Therefore,
Substituting values, we have:

Simplifying, we have:
![[(2^2) (-1^2)] - [(-3^2)(2-1)]](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wsk7k4rjl25rzsp8kh36p074yeok485qy1.png)
![= [(4) (1)] - [(9)(1)]](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xs6kui32sl0vd0amsdtbjf5x2reaqh07p9.png)

= -5
The correct answer is option B